Near‐Field Orbital Angular Momentum Generation and Detection Based on Spin‐Orbit Interaction in Gold Metasurfaces. Issue 10 (22nd August 2019) - Yang, Hui; Chen, Zhiquan; Liu, Qing; Hu, Yueqiang; Duan, Huigao
Abstract: Light carrying orbital angular momentum (OAM) is widely accepted as a promising carrier for high‐speed information communications, in which the generation and detection of OAM is a vital issue. Although the generation and detection of OAM in free space is well investigated, further extensions to near‐filed surface plasmon polariton (SPP) would be crucial for miniaturing and integrating platforms. Here, based on spin‐orbit interaction, a general scheme for near‐filed generating and detecting OAM modes is numerically and theoretically demonstrated. Utilizing the proposed design scheme, SPP OAM modes with optional topological charges can be achieved, which offers a new approach to generate near‐field OAM modes. To characterize the physical mechanism of spin‐orbit interaction, an improved dipole model is established for the first time, from what is known, with which the numerical results are well reproduced. Moreover, with elaborately design, the OAM generators can be developed into a compact OAM detector. Such a device owns the capacity of simultaneously discriminating the sign, the topological charge and the helicity of the incident OAM beam via a single measurement. These results provide a general method for near‐field OAM generation and detection, indicating promising applications in optical communication, particle trapping, and integrated photonic circuits. Abstract : Based on spin‐orbit interaction, a general scheme for near‐filed generating and detecting OAM modes, is numerically and theoretically demonstrated via ultra‐thin plasmon metasurfaces. The proposed compact OAM detector owns the capacity of simultaneously discriminating the sign, the topological charge and the helicity of the incident OAM beam via a single measurement.